THE LECTURERS’ WRITTEN CORRECTIVE FEEDBACK IN WRITING CLASSES: UNIVERSITY STUDENTS’ OPINIONS AND PREFERENCES - Witari, Putu Sita; Mahardika, Agustine Andriana Ayu (Journal of English Language and Culture, 2024)
Writing in English for university students who use English as their second or foreign language can be challenging. This is not only because of the linguistic aspects that may be different from their first language but also because of the non-linguistic aspects such as the content, knowledge, and structure. For such cases, the involvement of a lecturer in their learning process is essential and this can be done by providing written corrective feedback (WCF) to their writing. In order to investigate the university students’ opinions of written corrective feedback and the types of it that are preferred in their writing classroom, this study hence is conducted to gain a better understanding from the students’ point of view. By implementing mixed-method research, the findings revealed major outcomes. Results showed that students generally felt positive about receiving WCF, as it helped identify errors, progress, and weaknesses. However, they felt that WCF alone was insufficient, and a combination of written corrective feedback and verbal feedback was more beneficial. Moreover, the students prefer direct feedback over indirect feedback to build awareness and knowledge about their writing process. They are impartial towards metalinguistic feedback and prefer correction forms with explanations. Lecturers' writing feedback develops critical thinking and revision strategies, encouraging students to research and read widely. Future studies could include longitudinal studies with teacher and student opinions, class observation, and technological advancements, aiming to stimulate new perspectives on written corrective feedback in EFL classrooms.